Comparative Study of Durability and Microstructure Properties of Concrete made with Different Grades of Nigerian Portland Limestone Cement - Fapohunda, C. A.; Famodimu, B. I.; Adigo, B. C.; Jeje, A. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
It is now becoming apparent that concrete should not only be strong but must also be durable. It is also believed that understanding the microstructure of the concrete will help produce strong and durable concrete, and thus enhance innovativeness in concrete application. This paper compares the durability performance and microstructure development of concrete produced with Portland limestone cement (PLC) grades 32.5R and 42.5R. The durability investigation was accomplished through coefficient of water absorption and sorptivity measurements. The scanning electron microscopy (SEM) was used to investigate the microstructure of the concrete samples.  The results show that concrete produced with cement grade 42.5R showed higher durability potential than the ones produced with grade 32.5R using 28 days curing period. Similarly, it was also observed that concrete specimens produced with 32.5R and with water/cement ratio of 0.40 have better durability index at the later dayscuring of 90 days in comparison to grade 42.5R concrete specimens.  It can be concluded that concrete produced using grade 42.5R cement has potential for better durability performance in relation to concrete produced with 32.5R